Simulation of the Electro-hydraulic Control of Wet Clutch Actuator - Zhang Zengliang (Jixie chuandong)
To the problems of strong nonlinear,time delay and lower control accuracy of wet clutch actuator,an automobile automatic transmission with wet clutch actuator is studied,according to the characteristics of the wet clutch and control strategy requirement,a wet clutch electro-hydraulic actuator control model is established,the simulation is carried out with Matlab/Simulink software.The results show that the charge phase,the displacement of electric hydraulic valve plunger and clutch,the clutch flow to achieve maximum positive displacement first,and gradually decreases stabilized.In the discharge phase,the displacement of electric hydraulic valve plunger and clutch,the clutch flow to achieve maximum negative displacement first,and gradually increased to stabilize,and the overall trend is consistent with the input current.In different times have different average delay time,and the delay time will reduce the control precision control of systems.The different control accuracy generate in different controllers and predictive control policies.